Implementasi Visualisasi Log Server Web dengan ELK Stack: Analisis Kasus Log Akses pada Sistem Elena di Sekolah Tinggi Teknologi Terpadu Nurul Fikri - Karmila, Hera; Saptono, Henry (Jurnal Informatika Terpadu, 2024)
Nurul Fikri Integrated Technology College (STT NF) is a higher education institution that focuses on the field of information technology. STT NF has a web-based online learning system which is also called E-Learning by the name of Elena. Elena's system can be accessed online where the activity will be recorded by the server in the form of access log data. The access log data contains information on the user's IP, access time, requests sent, website browser used and others. Access logs contain useful information for monitoring server performance and more. However, Elena's system has problems in the form of access log data which is in text form which makes it difficult to read and the amount of data is large. Based on this, this study aims to provide a system that is used to store, process and visualize Elena STT NF system log access data automatically using a script The method used in this research is the development research method. The results obtained in this study are visualization in the form of important information from Elena's system log access data. In this research through several stages of research namely analysis, design, implementation, and testing. In the visualization test, the results were 100% and the test sending log data to Elasticsearch obtained 100% results, so that this research was implemented effectively.